Characterization of agroecosystems with sheep production in the eastern side of Yucatán, Mexico. - Candelaria-Martínez, Bernardino; Flota-Bañuelos, Carolina; Castillo-Sánchez, Luis Enrique (Agronomía Mesoamericana, 2015)
The aim of this study was to characterize and group agroecosystems with sheep production in the eastearn side of Yucatan, Mexico. This study was held from August 2012 to April 2013. A semi-structured questionnaire was applied while interviewing 93% of producers from seven municipalities that have sheep within their agroecosystems. Random sampling, cluster analysis, ANOVA using GLM and comparison of means by Tukey (P>0.05) were performed. Four different groups of agroecosystems with sheep production were obtained: GA (elderly people in charge, middle schooling, and high amount of land, large herds or more years practicing sheep farming), GB middle age people in charge, higher schooling, intermediate amount of land, and intermediate herd size), GC (elderly people in charge, less schooling, low amount of land and reduced herd size), and GD (younger people in charge, high schooling, low amount of land, small herd size and less time performing the activity). Sheep farming was the first, second, and third productive option for 12%, 75% and 11,8% of producers. In some cases, sheep production in the region has been practiced for over 15 years; however it is the economic priority only of a small group of producers. Access to resources determined their level of development and lack of organization among sheep producers is evident.